In vitro sensitivity testing of acanthamoeba clinical isolates from patients with keratitis against polyhexamethylene biguanide (PHMB) and chlorhexidine - Abdullah N.S.; Ghani M.K.A.; Nordin A.; Suboh Y.; Rahim N.A.; Ahmad N. (2024)
Indexed by WOS/SCOPUS